Efektivitas Pelayanan Surat Izin Mengemudi (SIM) Pada Polisi Resor Kota Ternate - Hajuan, Andi (Journal of Government Science Studies, 2022)
Deskripsi, effectiveness service of SIM at Polres Town of Ternate run in this time not yet is effective, because, service of SIM not yet as according to Code/Law procedure of No. 22 Thn 2009, and service of SIM there are two way of service that is passing shoot and tes, but which is run in this time more tend to to SIM shoot. Result of which is found in this research is service which not yet as according to mechanism / procedure not yet is effective. Service not yet as according to Code/Law of No. 22 Thn 2009, provided counter still is limited, there no coherent guidance to follow SIM tes. All service of SIM more tend to to SIM shoot, therefore the importance of the institute have the character of tranparansi, professional, trust and existence of performance evaluation. So that in execution of service of SIM can walk according to procedure.